Three dimensional reconstruction of the hyobranchial apparatus of Hyla nana tadpoles (Anura: Hylidae) - Vera Candioti, María Florencia (2004)
This study describes the hyobranchial skeleton and branchial musculature of Hyla nana tadpoles, employing three-dimensional reconstruction from histological sections. The cartilaginous skeleton is characterized by a marked development of the ceratohyals and a reduction of the branchial basket. The muscular topology is congruent with the pattern found in most hylines, with particular features such as the m. subarcualis rectus I with only two heads (dorsal and ventral), and a discontinuous m. subarcualis rectus II-IV, inserted anterolaterally in the ceratobranchial I. Such features, infrequent among hylids, are presumably shared by other species within the H. microcephala group.